Transformação de Setaria viridis e Saccharum spp. com o gene MATE visando tolerância ao alumínio - Ribeiro, Ana Paula (2016)
A major limiting factor for plant growth is the aluminum (Al) toxicity displayed by acidic soils, especially in tropical regions. In Brazil, sugarcane is an economically important crop, for sugar, bioethanol and production. The expansion of the arable lands for sugarcane production in Brazil includes the Cerrado region, characterized by acidic soils and consequently high Al toxicity. Under high levels of aluminum in the soil, the root growth is restricted, and in such conditions, the roots are unable to explore deeper regions of the soil for the absorption of nutrients and water, with major yield losses. Thus, it is pivotal the development of new varieties of crops presenting aluminum tolerance. In this work, the model plant Setaria viridis A10.1 was transformed to generate transgenic plants with aluminum tolerance. S. viridis is a short, fast-growing, C4 plant with its genome sequence fully available, making it a reliable model for genetic studies. In addition, S. viridis is suitable for genetic transformation through Agrobacterium tumefaciens, with well-established transformation protocols. The idea was to use this model plant as a proof of concept for sugarcane, which has a complex genome and therefore it is less amenable for genetic transformation. The plants were transformed to overexpress a gene that belongs to the Multidrug And Toxic Compound Extrusion Family (MATE), which confers aluminum tolerance in sorghum (Sorghum bicolor). The sorghum MATE (SbMATE) is a membrane transporter responsible for the efflux of citrate to the rhizosphere, chelating Al 3+ ions, and consequently decreasing the toxicity of this metal. Here, we describe the genetic transformation of S. viridis with an orthologous of SbMATE, the BdMATE gene. In addition, the development of a hydroponic bioassay for Al stress and the phenotyping of the transformed plants are also described. The transgenic plants showed an Al-tolerance phenotype, characterized by sustained root growth under {20} µM Al 3+ , whereas nontransformed plants showed root growth inhibition. These promising results obtained in S. viridis prompted us to genetically transform sugarcane plants overexpressing SbMATE for Al tolerance.